Age-Specific Entrepreneurship and PAYG Public Pensions in Germany - Burkhard Heer; Mark Trede (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We present new empirical evidence on the distribution of earnings, income and wealth among entrepreneurs in Germany. We document that both earnings and income are more concentrated among entrepreneurs than among workers and describe a large-scale overlapping-generations model that can replicate these findings. As an application, we compute the equilibrium effects of a reform of the German pay-as-you-go pension system in which entrepreneurs must also contribute and receive a pension. We show that in the presence of mobility between workers and entrepreneurs, the expected lifetime utility of all newborn households unanimously declines due to the general equilibrium effects of lower aggregate savings, and welfare losses amount to approximately 5% of total consumption. In addition, the integration of self-employed workers into the social security system in Germany does not help to improve its fiscal sustainability, and only an increase in the retirement age to 70 years will help to finance pensions at the present level beyond the year 2050.
Keywords: H55; D31; D91; J11; L26; C68; 330; entrepreneurship; aging; income distribution; overlapping generations; social security; fiscal sustainability